Analysis of the planning and development strategy of the digital printing machine business X - Federico, Rafael; Hapsari , Ajeng Andriani (ProBisnis : Jurnal Manajemen, 2025)
The digital printing machine business is a business in the printing sector that focuses on selling digital printing machine equipment to those involved in printing activities and has a central operation in Tangerang. This business continues to run because the increasing need for packaging to meet people's interest in opening SMEs has made the digital printing market increasingly growing. Using various digital platforms as promotional media for PT. X targets the national market. This study aims to evaluate and find out the appropriate development to be carried out in the future by PT. X is reviewed from the marketing aspect, financial aspect, operational aspect, strategic aspect and human resources aspect. Evaluation and development studies are carried out by analyzing various aspects to find out the right strategy for carrying out development